Spontaneous regression of mismatch repair‐deficient colorectal cancers: Case series. Issue 1 (26th June 2020) - Utsumi, Takahiro; Miyamoto, Shin'ichi; Shimizu, Takahiro; Yokogawa, Kasumi; Nakanishi, Yuki; Nikaido, Mitsuhiro; Hirata, Ayako; Nishida, Miyu; Aoyama, Ikuo; Okuno, Tomoko; Yoshizawa, Akihiko; Kaneda, Akihiro; et al.
Abstract : Spontaneous regression (SR) has been reported in various malignant tumors. However, SR in colorectal cancer (CRC) is particularly rare and the mechanism remains unclear. We here report three cases of CRCs displaying SR, which were experienced at two institutions. Intriguingly, all of these cases displayed the common endoscopic characteristics; superficial elevated lesion accompanied by a central depression (0‐IIa + IIc, in the Paris classification), with a nonpolypoid growth, located in the ascending colon. Furthermore, immunohistology of biopsy specimens revealed the lack of DNA mismatch repair proteins within the CRC lesions, suggesting that these were mismatch repair‐deficient (dMMR) CRCs. One of the major features of dMMR cancers is an increase in the number of tumor‐infiltrating lymphocytes. Thus, the dMMR phenotype might be associated with SR of CRCs through the activation of anti‐tumor host immune responses.